Consistent temporal variation in the diet of an endangered alpine lizard across two south‐eastern Australian sky‐islands. (28th December 2017) - Atkins, Zak S.; Clemann, Nick; Schroder, Mellesa; Chapple, David G.; Davis, Naomi E.; Robinson, Wayne A.; Wainer, John; Robert, Kylie A.
Abstract: A species' diet and feeding strategy directly affect fitness and environmental interactions. Understanding spatial and temporal variation in diets can identify key resources, inform trophic relationships, and assist in managing threatened species. The nationally endangered Guthega skink, Liopholis guthega, is restricted to two isolated Australian alpine plateaux, the Bogong High Plains (BHP) in Victoria and Kosciuszko National Park (KNP) in New South Wales. We compared this species' foraging ecology over the summer period between these 'sky‐islands' separated by 100 km of lowland valleys. Scat composition did not differ between the two lizard populations, despite differences in the invertebrate assemblages present. However, L. guthega diet varied temporally over summer at both locations. Invertebrates, predominantly Hymenoptera and Coleoptera, were the dominant food group in early summer (78% volume (V), 100% frequency occurrence (F)) and mid‐summer (80% V, 100% F). A significant dietary shift occurred in late summer, when lizards consumed predominantly plant material (63% V, 95.5% F), consisting primarily of seasonally abundant berries from the snow beard heath, Acrothamnus montanus . In contrast to similar‐sized Egerniinae species, it appears L. guthega is capable of opportunistically shifting its diet towards plant material in response to temporal variation in resource availability. Furthermore, the prevalence of intact seeds in scats indicates L. guthega may play a significant role in seed dispersal. Understanding these trophic interactions will assist conservation management of L. guthega, allowing conditions for an already established captive colony to mimic the temporally variable diets present in situ, as well as informing revegetation initiatives aimed at maintaining and expanding wild populations.